Uniqueness of large solutions for non-monotone nonlinearities. (June 2019) - López-Gómez, Julián; Maire, Luis
Abstract: In this paper we construct a general class of non-monotone positive nonlinearities, f ( u ), for which the differential equation u ′ ′ = f ( u ) has a unique large solution in ( − T, T ) . In most of the available literature it is required f ( u ) to be strictly increasing in order to establish the uniqueness of the large solution.